Knockdown of LncRNA SCAMP1 suppressed malignant biological behaviours of glioma cells via modulating miR‐499a‐5p/LMX1A/NLRC5 pathway. Issue 8 (17th June 2019) - Zong, Zheqi; Song, Yichen; Xue, Yixue; Ruan, Xuelei; Liu, Xiaobai; Yang, Chunqing; Zheng, Jian; Cao, Shuo; Li, Zhen; Liu, Yunhui
Abstract: Dysregulation of long non‐coding RNAs (lncRNAs) confirm that it plays a crucial role in tumourigenesis and malignant progression of glioma. The present study demonstrated that LncRNA secretory carrier membrane protein 1 (SCAMP1) was up‐regulated and functioned as an oncogene in glioma cells. In addition, miR‐499a‐5p was down‐regulated meanwhile exerted tumour‐suppressive function in glioma cells. Subsequently, inhibition of SCAMP1 significantly restrained the cell proliferation, migration and invasion, as well as promoted apoptosis by acting as a molecular sponge of miR‐499a‐5p. Transcription factor LIM homeobox transcription factor 1, alpha (LMX1A) was overexpressed in glioma tissues and cells. Moreover, miR‐499a‐5p targeted LMX1A 3′‐UTR in a sequence‐specific manner. Hence, down‐regulation of SCAMP1 remarkably reduced the expression level of LMX1A, indicating that LMX1A participated in miR‐499a‐5p‐induced tumour‐suppressive effects on glioma cells. Furthermore, knockdown of LMX1A decreased NLR family, CARD domain containing 5 (NLRC5) mRNA and protein expression levels through directly binding to the NLRC5 promoter region. Down‐regulation of NLRC5 obviously inhibited malignant biological behaviours of glioma cells through attenuating the activity of Wnt/β‐catenin signalling pathway. In conclusion, our study clarifies that SCAMP1/miR‐499a‐5p/LMX1A/NLRC5 axis plays a critical role in modulating malignant progression of glioma cells, which provide a novel therapeutic strategy for glioma treatment.